2012
DOI: 10.1111/adb.12001
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of baclofen and oxytocin on the increased ethanol consumption following chronic psychosocial stress in mice

Abstract: Chronic stress is known to enhance the susceptibility for addiction disorders including alcoholism. While these findings have been recapitulated in animal models, the majority of these studies have utilized non-social rather than social stress paradigms; the latter of which are believed to be more relevant to the human situation. Therefore, the major aim of this study was to investigate, if 14 days of chronic subordinate colony housing (CSC), a pre-clinically validated psychosocial stress paradigm relevant for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 50 publications
3
51
0
4
Order By: Relevance
“…Along the same line, Peters and colleagues were able to show that shorter stress periods produced the same effect. In fact, following 14 days of chronic subordinate colony housing, the CSC mice consumed significantly more ethanol than SHC controls (Peters et al 2013). However, to our knowledge, this is the first study to report that CSC housing-induced chronic psychosocial stress produces reinstatement of ethanol-induced CPP behavior.…”
Section: Consequences Of Csc On Body Weight Gain and Anxiety-like Behmentioning
confidence: 64%
See 1 more Smart Citation
“…Along the same line, Peters and colleagues were able to show that shorter stress periods produced the same effect. In fact, following 14 days of chronic subordinate colony housing, the CSC mice consumed significantly more ethanol than SHC controls (Peters et al 2013). However, to our knowledge, this is the first study to report that CSC housing-induced chronic psychosocial stress produces reinstatement of ethanol-induced CPP behavior.…”
Section: Consequences Of Csc On Body Weight Gain and Anxiety-like Behmentioning
confidence: 64%
“…This has been recapitulated in animal models, but most studies have utilized non-social rather than social stress paradigms, of which the latter are believed to be more relevant to the human situation, mainly for a lack of appropriate animal models. Nevertheless, recent studies have found that chronic psychosocial stress in mice induces an anxiogenic-like phenotype and enhances alcohol consumption and preference (Bahi 2013a;Peters et al 2013) as well as ethanol-induced conditioned place preference (EtOH-CPP) (Bahi 2013a). Animal studies reporting a positive correlation between stress and alcohol consumption suggest that drinking may take place in response to chronic stress if it is perceived as unavoidable (Nash and Maickel 1988;Volpicelli 1987), when alternative resources are lacking, when alcohol is accessible, and when the individual believes that alcohol will help to reduce the stress (Jennison 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Es wird spekuliert, dass sich die Wirkung von Baclofen durch die Aktivierung von Oxytocinneuronen im PVN entfaltet [49,50].…”
Section: Oxytocin Im Einsatz Gegen Suchtmechanismenunclassified
“…Importantly, McGregor and Bowen reported lasting reduction (at least 6 weeks) in "Vodka Cruiser" preference (relative to 3% sucrose) in male and female alcohol preferring rats following a single administration of oxytocin (1 mg/kg) [4]. Recently, Peters and colleagues reported that, following 2 weeks of a two-bottle free choice continuous access of increasing concentrations of ethanol, systemic oxytocin (10 mg/kg) administration reduced the alcohol intake in single housed mice but not in stressed counterparts [27]. In humans, and compared to placebo, intranasal oxytocin given twice daily for 3 days in alcohol-dependent subjects, during a double-blind clinical trial, reduced alcohol withdrawal symptoms and reduced the amount of lorazepam administered "as needed" during detoxification [6].…”
Section: Introductionmentioning
confidence: 99%